Lengthening single-stem rotation improves biomass yield and water use efficiency in black poplar genotype multi-stem rotation coppice plantations. (November 2021) - Saulino, Luigi; Allevato, Emilia; Rossi, Sergio; Minotta, Gianfranco; Fiorentino, Nunzio; Saracino, Antonio
Abstract: Poplar short rotation coppice (SRC) plantations have great potential for supplying environmentally friendly bio-based industries. However, little research has focussed on the linkages between SRC management regimes and the consumption of water for biomass production in the Mediterranean environment. Therefore, we compared six hybrid clones and four native black poplar genotypes with an aim to examine how two different lengthening periods (3 vs. 5 years) of single-stem rotation affected growth performance in the following three years of multi-stem rotation coppice. To achieve this goal, we assessed the aboveground dry biomass production and variation in water use efficiency (WUE) of the genotypes annually. A longer single-stem rotation increased biomass productivity and WUE in the multi-stem rotation of the native black poplar, rather than that of the hybrid genotypes. In contrast, biomass and WUE performances did not diverge between the native and hybrid genotypes under the shorter single-stem phase. These findings underline the importance of lengthening the rotation of single-stem SRC plantations in hot and dry Mediterranean climates. Native black poplar genotypes managed in SRC should be strongly considered as environmentally compatible genetic resources both in protected areas and in areas where water supply constrains biomass production. Highlights: Lengthening single-stem rotation improves yield of wild black poplar genotypes. Wild black poplars represent an alternative to studied hybrid clones in Mediterranean climate. Black poplar genotypes with high WUE enhance sustainability of SRC crop system.